Suicidal Ideation and Traumatic Exposure Should Not Be Neglected in Epileptic Patients: A Multidimensional Comparison of the Psychiatric Profile of Patients Suffering From Epilepsy and Patients Suffering From Psychogenic Nonepileptic Seizures - Guillen, Abel; Curot, Jonathan; Birmes, Philippe Jean; Denuelle, Marie; Garès, Valérie; Taib, Simon; Valton, Luc; Yrondi, Antoine (Frontiers in Psychiatry, 2019)
Introduction: Patients with Psychogenic Non-Epileptic Seizures (PNES) have often been exposed to traumatic events, which is a risk factor for suicidal behaviour. This would suggest that the severity of suicidal ideation is greater in PNES than in patients suffering only from epileptic seizures (ES). However, these psychiatric symptoms may be underestimated in the ES population. The specific features or similarities between the psychiatric clinical profiles of these two groups should be elaborated to improve therapeutic management. Our study is the first to compare suicidal ideation, suicide risk, post-traumatic stress disorder (PTSD) and depression disorder simultaneously in both groups, in a tertiary care epilepsy centre. Material and methods: We prospectively enrolled patients hospitalised for video-EEG monitoring to assess repeated seizures before an ES or a PNES diagnosis was made. During the psychiatric consultation that accompanied the video-EEG, we rated the severity of suicidal ideation and depressive symptoms, suicidal risk, traumatic exposure history and PTSD symptoms. Results: Eighteen subjects were enrolled and diagnosed with PNES, and 42 with ES. The PNES group reported more exposures to traumatic events and more intense PTSD symptoms (median: 17 vs. 27; p=0.001). The severity of suicidal ideation did not differ significantly between the two groups. Conclusion: It is the severity of PTSD symptoms in PNES patients that differentiates them from ES patients, although exposure to traumatic events is also frequent in ES patients. We demonstrated that suicidal ideation and suicide risk are equally high in the ES and PNES groups. Therefore, both groups require extreme vigilance in terms of suicidal risk.